AUGMENTED REALITY AND AI IN PUBLIC ART MANAGEMENT - Putra, Riyan Sisiawan; Juneja, Bhanu; Kumari, Hanna; Kaushik, Nares; Dwibedi, Rajat Kumar; Rawat, Kalpana; Barkade, Shrikant Shrimant (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Public art management is becoming increasingly challenged by the swift urbanization, disjointed governance, a lack of interaction with the audience, and a requirement to make data-driven decisions. Artificial Intelligence (AI) and Augmented Reality (AR) have the potential to revolutionize the way people visualize, plan, and monitor and experience public artworks. In this paper, the author suggests an AR-AI framework of managing the public art that involves the fusion of immersive spatial visualization, intelligent analytics, and another aspect of automation. Based on the idea of the public art management theory, urban cultural policy, and digital placemaking, the framework allows simulating artwork placement in the actual situation in urban environments, evaluating the site appropriateness with the help of machine learning, and tracking the state of the artwork with the help of computer vision analysis. The natural language processing modules can also assist participatory governance by helping to extract sentiment, theme, and concerns of public feedback in various digital platforms. The proposed system will combine heterogeneous data sources such as geospatial data, environmental factors, engagement by the audience and cultural metadata to provide evidence-based decision-making at every stage of the artwork lifecycle. In addition to the efficiency in operations, AR-based storytelling and pedagogical overlay contribute to the cultural interpretation, access, and civic participation. Ethical issues, such as privacy in surveilled public places, bias in cultural algorithms, and sustainability of technologies in the long-term, are also critically assessed in the study.